The Motivational Impact of Nicotine and its Role in Tobacco Use - Bevins, Rick A. (Springer, 2017)
Tobacco kills more people worldwide than any legal or illegal drug; the collective benefits of quitting smoking are plentiful, from improved health, increased life expectancy, and fewer sick days to less stress on families and health care providers. Tobacco use and addiction depend on the complex interplay of neurochemical, genetic, personal, and social factors—and nicotine, as the principal psychoactive ingredient in tobacco smoke, stands at the center of this equation.